Synthesis and in vivo evaluation of gallium‐68‐labeled glycine and hippurate conjugates for positron emission tomography renography. (29th December 2014) - Pathuri, Gopal; Hedrick, Andria F.; January, Spenser E.; Galbraith, Wendy K.; Awasthi, Vibhudutta; Arnold, Charles D.; Cowley, Benjamin D.; Gali, Hariprasad
<x xml:space="preserve">Abstract</x> The objective of this study was to evaluate four new 68Ga‐labeled 1, 4, 7, 10‐cyclododeca‐1, 4, 7, 10‐tetraacetic acid (DOTA)/1, 4, 7‐triazacyclononane‐1, 4, 7‐triacetic acid derived (NODAGA)‐glycine/hippurate conjugates and select a lead candidate for potential application in positron emission tomography (PET) renography. The non‐metallated conjugates were synthesized by a solid phase peptide synthesis method. The 68Ga labeling was achieved by reacting an excess of the non‐metallated conjugate with 68GaCl4− at pH −4.5 and 10‐min incubation either at room temperature for NODAGA or 90 °C for DOTA. Radiochemical purity of all 68Ga conjugates was found to be >98%. 68Ga‐NODAGA‐glycine displayed the lowest serum protein binding (0.4%) in vitro among the four 68Ga conjugates. Biodistribution of 68Ga conjugates in healthy Sprague Dawley rats at 1‐h post‐injection revealed an efficient clearance from circulation primarily through the renal–urinary pathway with <0.2% of injected dose per gram remaining in the blood. The kidney/blood and kidney/muscle ratios of 68Ga‐NODAGA‐glycine were significantly higher than other 68Ga conjugates. On the basis of these results, 68Ga‐NODAGA‐glycine was selected as the lead candidate. 68Ga‐NODAGA‐glycine PET renograms obtained in healthy rats suggest 68Ga‐NODAGA‐glycine as a PET alternate of 99mTc‐Diethylenetriaminepentaacetic acid (DTPA).